Effectiveness of the Stimulation of Endorphin, Oxytocin, and Serotonin (SPEOS) Method in Improving Sleep Quality among Postpartum Women: A Quasi-Experimental Study in Primary Maternal Healthcare in Gorontalo, Indonesia - Ani Retni; Fatmah M Abdullah (Media Publikasi Cendekia Indonesia, 2026)
Postpartum sleep disturbance is a clinically relevant maternal health problem because it may weaken physical recovery, emotional regulation, breastfeeding continuity, and early mother infant adaptation. This study analyzed the effectiveness of the Stimulation of Endorphin, Oxytocin, and Serotonin (SPEOS) method in improving sleep quality among postpartum women in the working area of Telaga Primary Health Center, Gorontalo, Indonesia. A quasi-experimental pretest and posttest control group design using consecutive sampling and convenience sub-district cluster allocation was used. Sixty-two postpartum women were allocated into an intervention group and a control group (n = 31 per group). The intervention group received the home-based SPEOS method for seven consecutive days, whereas the control group received routine postpartum care. Sleep quality was measured using the Pittsburgh Sleep Quality Index. Because the data were not normally distributed, the Wilcoxon Signed Rank Test and Mann Whitney U Test were applied. After the intervention, mild sleep disturbance in the intervention group increased from 16.1% to 83.9%, while severe sleep disturbance was no longer observed. Wilcoxon tests revealed significant PSQI reductions in the intervention group (Z = -4.564; p < 0.001; r = 0.82). The Mann Whitney U Test also demonstrated a significant difference in score change between groups (U = 118.500; Z = -4.921; p < 0.001; r = 0.62). These findings indicate that SPEOS provides a statistically and clinically meaningful non-pharmacological approach for postpartum sleep restoration. Its effect is hypothesized to be linked to pathways involving tactile relaxation, oxytocinergic activation, endorphin release, reduced stress response, and increased maternal comfort. SPEOS is recommended as a feasible midwife-led community-based intervention in postpartum nursing and midwifery care.